(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2019)
Â In this study, a wideband double slot antenna is introduced. The proposed monopole antenna is designed using the theory of characteristic mode for slot monopoles. A circular shape is used as the initial design stage, to enhance the bandwidth, two circular slots are employed. Four modes have been excited to gain a physical insight and to find out which mode is dominant. The design and analysis were completed utilizing both the time domain and multilayer solver in CST 2017, without considering the feeding port. An antenna model in UWB frequency is constructed. Experimented and simulated results shows that the proposed planar structure has a wide impedance width with good radiation characteristics.